Surgery of early stage breast cancer in older women – multicenter study and review of 143 cases - Saad Abdalla, Abdalla; Adamczyk, Beata (Journal of Medical Science, 2017)
Most of breast cancers are diagnosed in females over 50 years of age, however it is found that about 30% of the disease diagnosed with women above 70 years. Generally speaking, those patients is treated with a smaller range of treatment which usually offered to the younger group of patients. Despite the presence of many comorbidities, however the patient may still have a good physiological reserve, which make offering a radical surgery of the cancer very possible. Age should not be a determinant for quality of care in breast cancer. In this paper, we looked to 143 breast cancer patients with age >70 years had been operated. The oldest was 86. ASA assessment tool used Pre-operatively. Mastectomy done in 70% where 30% underwent Breast Conservation Surgery. Axillary surgery done in 94% of cases (52% Sentinel lymph node biopsy and 42% axillary clearance). The histology of the removed cancers showed invasive ductal carcinoma in 76% of cases, invasive lobular carcinoma in 11%, with DCIS in 06%. After surgery, every patient has been offered the individual suitable adjuvant treatment as chemotherapy, radiotherapy, Herceptin or hormonal manipulation. As those patients can stand the radical surgery and live with a good life quality after treatment, we advise to extend the screening program beyond the current recommended age. Also we recommend further research to understand more about the biology of the breast cancer in the older age group and disseminate geriatric assessment tool as Adult Co-morbidity Evaluation (ACE-27) to provide a proper evaluation of the patient status prior to final management decision.
Keywords: breast cancer; mastectomy; breast conservation surgery